2016
DOI: 10.2147/ijwr.s112029
|View full text |Cite
|
Sign up to set email alerts
|

The effect of organic acids and sulfur dioxide on C4 compound production and &beta;-glucosidase activity of <em>Oenococcus oeni</em> from wines under acidic conditions

Abstract: The purpose of this work was to investigate the effect of l-malic and citric acids and SO 2 on two biochemical properties (diacetyl/acetoin/2,3-butanediol formation and β-glucosidase activity) relevant to flavor development in six Oenococcus oeni strains from wines at pH 4.8 and 3.8. Cells were cultured in MRS without citrate (control medium) and combined with l-malic acid (2 g/L), citric acid (0.7 g/L), and SO 2 (80 mg/L) at pH 4.8 and 3.8. All the test strains grew at all conditions tested including in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Numerous studies had been conducted, providing evidence of the potential βG activity of O. oeni strains for flavor enhancement in wines [7,10,[14][15][16][17][18][19][20][21][22][23][24]. These studies demonstrated that possession of βG activity is widespread and extent of βG activity is strain dependent among O. oeni strains [16,21,25,26], and the enzyme activity is mainly affected by pH, temperature, sugar, and ethanol concentration [15][16][17]19,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies had been conducted, providing evidence of the potential βG activity of O. oeni strains for flavor enhancement in wines [7,10,[14][15][16][17][18][19][20][21][22][23][24]. These studies demonstrated that possession of βG activity is widespread and extent of βG activity is strain dependent among O. oeni strains [16,21,25,26], and the enzyme activity is mainly affected by pH, temperature, sugar, and ethanol concentration [15][16][17]19,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated that possession of β G activity is widespread and extent of β G activity is strain dependent among O . oeni strains [ 16 , 21 , 25 , 26 ], and the enzyme activity is mainly affected by pH, temperature, sugar, and ethanol concentration [ 15 17 , 19 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…These fruits undergo a period of fermentation where microbiological processes contribute significantly to the final quality of the product. 1 Wine usually has an alcohol content ranging between 5 to 13 percent. Wine has a flavour like fresh fruit which could be stored and transported under the existing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…151 Page 2 of 12 of wine (Maturano et al 2016;Tristezza et al 2016). Microbiological stability and flavor modification of wine are also outcomes of MLF with a broad range of secondary compositional changes that include amino acids and polyols metabolism, esters synthesis and glycosides hydrolysis (Bartowsky et al 2002;Liu 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, Mansfield et al (2002) reported the production of β-glycosidase enzyme in O. oeni strains, although their culture failed to hydrolyze native grape glycosides. In addition, several studies have focused on the influence of pH, temperature, sugar and ethanol content on β-d-glucosidase activities of O. oeni (Boido et al 2002;D'Incecco et al 2004;Grimaldi et al 2005a, b;Bloem et al 2008;Gagné et al 2011;Maturano et al 2016). However, data are still scarce and often contradictory.…”
Section: Introductionmentioning
confidence: 99%